Properties of the Photometric Components of Lenticular Galaxies - J. Alfonso L. Aguerri (Advances in Astronomy)
After almost one century since their definition, the origin of lenticular galaxies is still a matter of debate. Several formation processes have been proposed in order to explain the wide variety of their observational properties. These properties could indicate that the class of lenticulars is a family formed by galaxies with different formations and evolutions. Here I review the main observational properties of the photometric components of lenticular galaxies reported in recent decades. I revise the main processes proposed in order to explain their origin and evolution. I also explain the different properties of the lenticular galaxies that have evolved through each of these formation processes. A unique opportunity for understanding the origin of S0 galaxies will shortly be forthcoming. This is due to the morphological classifications of large galaxy samples that have recently been published. These classifications have given us our first ever opportunity to study large samples of lenticulars within a wide range of masses and located in a great variety of environments. These large samples will provide us with a real census of nearby lenticular galaxies and could be crucial in finally helping us to understand the origin and evolution of these galaxies.